Fires, vegetation, and human - The history of critical transitions during the last 1000 years in Northeastern Mongolia - Słowiński, Michał; Obremska, Milena; Avirmed, Dashtseren; Woszczyk, Michał; Adiya, Saruulzaya; Łuców, Dominika; Mroczkowska, Agnieszka; Hałaś, Agnieszka; Szczuciński, Witold; Kruk, Andrzej; Lamentowicz, Mariusz; Stańczak, Joanna; et al. (My University, 2022)
Fires are natural phenomena that impact human behaviors, vegetation, and landscape functions. However, the long-term history of fire, especially in the permafrost marginal zone of Central Asia (Mongolia), is poorly understood. This paper presents the results of radiocarbon and short-lived radionuclides (210Pb and 137Cs) dating, pollen, geochemical, charcoal, and statistical analyses (Kohonen's artificial neural network) of sediment core obtained from Northern Mongolia (the Khentii Mountains region). Therefore, we present the first high-resolution fire history from Northern Mongolia covering the last 1000 years, based on a multiproxy analysis of peat archive data. The results revealed that most of the fires in the region were likely initiated by natural factors, which were probably related to heatwaves causing prolonged droughts. We have demonstrated the link between enhanced fires and “dzud”, a local climatic phenomenon. The number of livestock, which has been increasing for several decades, and the observed climatic changes are superimposed to cause “dzud”, a deadly combination of droughts and snowy winter, which affects fire intensity. We observed that the study area has a sensitive ecosystem that reacts quickly to climate change. In terms of changes in the vegetation, the reconstruction reflected climate variations during the last millennium, the degradation of permafrost and occurrence of fires. However, more sites with good chronologies are needed to thoroughly understand the spatial relationships between changing climate, permafrost degradation, and vegetation change, which ultimately affect the nomadic societies in the region of Central and Northern Mongolia.
Keywords: climate change; Mongolia; wildfire; permafrost; pingo; peat; human impact; Holocene; dzud; drought; vegetation change; paleoenvironment; macrofossils; pollen; geochronology; 210Pb; 137Cs; 14C; geochemistry; charcoal; climate reconstruction; peat accumulation